Occurence of dentinal defects after root canal preparation with R-phase, M-Wire and Gold Wire instruments: a micro-CT analysis - Marcely Cassimiro; Kaline Romeiro; Luciana Gominho; Andressa de Almeida; Larissa Costa; Diana Albuquerque (BMC, 2017)
Abstract Background This study aims to evaluate the frequency of dentinal defects after root canal preparation with the ProTaper NEXT, K3XF and WaveOne GOLD systems using microcomputed tomography. Methods Sixty permanent mandibular incisors with a single canal were selected. Inspection of the teeth was performed under a stereomicroscope (15x) to observe the presence of pre-existing cracks and fractures lines. Samples were divided into three experimental groups (n = 20): ProTaper NEXT (PTN), K3XF (K3XF) and WaveOne GOLD (WOG). Specimens were scanned through high-resolution microcomputed tomography before and after the preparation of the root canal. Subsequently, all the axial images were examined by two different methods to find possible dentinal defects. Furthermore, an analysis of each millimeter of ten apical millimeters was also performed. The absence or presence of dentinal defects was screened by 3 pre-calibrated blinded examiners. Results After analysing all 45,720 slices, dentinal defects were observed in 48,33% (22096 slices). PTN, K3XF and WOG groups represented 11,11% (5079 slices), 17,22% (7873 slices) and 20% (n = 9144) of the cross-sectional images, respectively. At 10 apical millimeters (600 slices), 33,33% (200 slices) presented some dentinal defects, representing 7,22% (43 slices), 13,33% (80 slices) and 12,77% (77 slices) of the cross-sectional images in the PTN, K3XF and WOG groups, respectively. All the dentinal defects presented in the postoperative images existed in the images prior to instrumentation. Conclusions There was no correlation between the preparation of a root canal using the PTN, K3XF and WOG systems and the formation of new dentinal defects.